2007
DOI: 10.1177/0269215507081573
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with a second hip fracture: a systematic review

Abstract: A number of easily observed risk factors may help identify those individuals at higher risk for subsequent fracture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 59 publications
1
43
0
2
Order By: Relevance
“…Higher risk of second fractures was reported among patients with cognitive impairment, lower bone mass, senile dementia, respiratory diseases, and alcoholism. [3,18,19] This study has several limitations. First, it was not possible to ascertain hip fractures that occurred before 2000.…”
Section: Discussionmentioning
confidence: 94%
“…Higher risk of second fractures was reported among patients with cognitive impairment, lower bone mass, senile dementia, respiratory diseases, and alcoholism. [3,18,19] This study has several limitations. First, it was not possible to ascertain hip fractures that occurred before 2000.…”
Section: Discussionmentioning
confidence: 94%
“…The reviews identified 3,5,9,10,14,17,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60] and their reference lists were the starting point for identifying both…”
Section: Scoping the Literaturementioning
confidence: 99%
“…5,9 Similarly, no single pathway provides the answers to all patient issues because of the complexity of comorbidities with which hip fracture patients can present. 8,29,49,240 Geriatric orthopaedic rehabilitation units are likely not to be cost-effective but can be beneficial for frailer patients to reduce complication rates, readmissions, nursing home placements and in-hospital deaths; however, they showed little effect on the rate of death post discharge, in both the short term and the long term.…”
Section: Comparison With Previous Literaturementioning
confidence: 99%
“…Previous studies have identified the various risk factors associated with the incidence of subsequent osteoporotic fractures, particularly for a second hip fracture (not assessed in this study) (Dretakis et al 1998;Saxena and Shankar 2000;Chapurlat et al 2003;Yamanashi et al 2005;Egan et al 2008;Angthong et al 2009;Mitani et al 2010). However, there is little information as to the risk factors for a subsequent osteoporotic vertebral compression fracture following an initial hip fracture.…”
Section: Discussionmentioning
confidence: 99%